Relationship of Destination Image, Sports Involvement, Event Quality, and Travel Motives as an Antecedent Factors on Revisit Intention in Recurring Running Sports-Event - Tara Setyaningtyas; Annesa Nariswari Kirana; Muhammad Angga Wicaksono (Bina Nusantara University, 2021)
The research aimed to examine the relationship between destination image, sports involvement, quality of sport events, and travel motives as antecedent factors to predict repeat visit intentions of marathon events. Data were collected using quantitative, non-probability, purposive sampling methods. The research instrument was an online questionnaire which was distributed to tourists and athletes who took part in running sport-events. Data analysis method used Structural Equation Modelling with Smart PLS 3.0. The test results show that not all research hypotheses are accepted. Sport-event quality (SQ) has a positive relationship but has no significant effect on revisit intention (RI) from repeated sporting events. The positive effect of travel motive (TM) on the intention to revisit a repetitive sporting event (RI) is proven. Travel motive (TM) also has a positive and significant effect on destination image (DI). Sports involvement (SI) has a positive and significant effect on revisit intention (RI). The same positive and significant effect is also shown in the relationship between sports event quality (SQ) and destination image (DI) variables. Revisit intention (RI) of repeated sporting events was found to be positively influenced by destination image (DI). There is a significant indirect effect of sport-event quality on intention to revisit repeated sporting events (RI), mediated by destination image.